Le peuple est-il soluble dans la constitution ? Leçons tunisiennes - Jean-Philippe Bras (L’Année du Maghreb)
The purpose of our article is to elucidate the case of Tunisia, namely the transition from revolutionary moment when the people wanted a revolution, to constitutional moment, when the people-as-an-event became the people-as-areferent through the establishment of mechanisms of representation. Following an initial phase when the pressure of the street or rural areas was fully exercised on political bodies whose frail legitimacy was cobbled together from scraps of old constitutional order and a vague ambition to take on the revolutionary claim, the people who engaged in the revolution fell apart. They agreed to give up their “revolutionary status” and appoint an authority to continue the process of political change. In this act of surrender, they inevitably met with democratic disappointment and uncertainty about representation through elections. Also, the day after their election, members of the Constituent Assembly were faced with virulent debates on the scope and duration of the mandate entrusted to them by the voting people, who expressed their fear of having the revolution confiscated by poll winners (mainly members of the Islamic party Ennahda), who had not been, far from it, major players in the revolutionary moment. While the law of majority is a prerequisite for the establishment of democratic regimes, as Adam Przeworski recalled, it can only be justified ultimately by the co-presence of alternation mechanisms. In addition, as Hans Kelsen pointed out, the system must be supplemented by the establishment of a Constitutional Court, whose threat to intervene forces majority and minority parliamentarians to compromise. There are good reasons to observe closely how this omnipotent Constituent Assembly will exercise its constitutional and legislative mandate, and set the dates for organizing future legislative elections.